ANALISIS FOOD WASTE PASIEN RAWAT INAP DI RUMAH SAKIT UMUM DAERAH IBNU SINA KABUPATEN GRESIK - Elok Mumpuni; Mas'udatus Saniyah (Universitas Muhammadiyah Gresik, 2021)
Food waste is still a problem in several hospitals in Indonesia because it is quite high, namely >20%. This causes the patient's food intake to be inadequate, resulting in length of hospitalization and increased patient morbidity and mortality. The purpose of this study was to determine the food waste in RSUD Ibnu Sina Gresik and its causal factors. This research uses descriptive analysis method with cross sectional study. The research subjects were 28 inpatients who were taken using simple random sampling technique. Data processing uses a visual estimation method (visual comstock) with a 6-point scale. The results showed that the most food waste of inpatients at Ibnu Sina Hospital, Gresik Regency was breakfast time with the most contributors being vegetables (>52%). The causative factors include in terms of food quality including a taste that is too salty, too sweet, bland, and an unattractive appearance. So it can be concluded that food waste is still relatively high and it is necessary to modify recipes or menus to increase the patient's preference for food.